FLOUTING MAXIM PERFORMED BY THE MAIN CHARACTER IN THE EDGE OF SEVENTEEN MOVIE - H, Tracy Rabecca; Lubis, Masdiana; Nasution, Ely Hayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
In this research, there are two objectives. First, to identify the kinds of flouting maxim performed by the main character in The Edge of Seventeen movie and Second, to find out the effect of flouting maxim performed by the main character in the movie. The method used in this research is descriptive qualitative method. The data of this research are twenty dialogues of The Edge of Seventeen movie which is containing flouting maxim. In analyzing the data, the researcher found that Nadine as the main character of the movie flouted all types of maxim. The most flouting maxim used by Nadine is floating maxim of quantity and, the least flouting maxim performed by Nadine are flouting maxim of quality and flouting maxim of manner. For the effects, Nadine gave seven effects based on Austin’s Perlocutionary effect theory to the other character of the movie. The seven effects based on Austin’s theory are annoying, boring, convincing, causing, getting the hearer realize something, getting the hearer to do something, and insulting. Further, the effect that mostly performed by Nadine in the movie is getting the hearer realize something effect.